Emotions: The Personality of the Spirit in the Old Testament - Rumbay, Christar Arstilo (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2022)
The existence of the Spirit has been received a long discussion in systematic theology, especially speaking, her existence in the Old Testament where the Spirit leaves less evidence of her personality. As the consequence, the personality of the Spirit has been shaken to discover its knowledge. This essay intends to grasp the personality of the Spirit in the Old Testament in which relates to her divinity and works. This article is a qualitative-descriptive, articles, books, and other related academic references are the main sources to construct the argumentation. Furthermore, tracing the emotions of the Spirit in the Old Testament is the main attention of this research and expected could offer a new perspective on how the Spirit, as a being, rather than a power, shares emotions; grieving, love, and shyness in the Old Testament.